2018
DOI: 10.1016/j.ijscr.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The lost stone — Laparoscopic exploration of abscess cavity and retrieval of lost gallstone post cholecystectomy: A case series and review of the literature

Abstract: HighlightsGallbladder perforation during laparoscopic cholecystectomy can cause late formation of intra-abdominal abscess.Gallbladder perforation should be informed and documented.We report a novel technique, using minimally invasive skills, to explore a small cavity of an abscess and retrieve lost gallstones.Laparoscopic exploration of the abscess cavity is not only safe and feasible, but enables meticulous exploration of the abscess cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Type of lost gallstones discovered during the re-intervention reported by 17 authors(20%), [ 18 – 20 , 24 , 31 , 35 , 39 , 42 , 43 , 53 , 54 , 63 , 80 ]; of those 7 (41%) were pigment and 8 (47%) cholesterol gallstones. Seventeen(20%) of authors reported the number of discovered gallstones [ 18 , 25 , 27 29 , 31 , 35 , 38 , 39 , 44 , 45 , 50 , 54 , 57 , 70 , 80 , 83 ]. The size of discovered gallstones was reported by 12(14.11%) authors [ 18 , 19 , 25 , 28 , 31 , 35 , 37 , 52 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Type of lost gallstones discovered during the re-intervention reported by 17 authors(20%), [ 18 – 20 , 24 , 31 , 35 , 39 , 42 , 43 , 53 , 54 , 63 , 80 ]; of those 7 (41%) were pigment and 8 (47%) cholesterol gallstones. Seventeen(20%) of authors reported the number of discovered gallstones [ 18 , 25 , 27 29 , 31 , 35 , 38 , 39 , 44 , 45 , 50 , 54 , 57 , 70 , 80 , 83 ]. The size of discovered gallstones was reported by 12(14.11%) authors [ 18 , 19 , 25 , 28 , 31 , 35 , 37 , 52 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In case this is not possible, efforts must be made to minimize spillage, trying to close the gallbladder with the grasp or with an endoclip. Proper irrigation and aspiration should be done and in case of stone spilling, surgeons must attempt to recollect all of them and extract them in an endobag [ 3 ]. If necessary, it is more advantageous to increase the dimension of the port for extraction than to risk spillage of gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being considered a safe procedure, it has intra-operative complications: gallbladder perforation (10-40%) and stone spillage (6-30%) are two of the most frequent ones [ 1 ]. Although initially thought that stone loss was harmless, it is now known to be associated with intra-abdominal complications, associated morbidity and mortality (0.04-19%) [ 2 ], despite the evidence that the majority of cases are asymptomatic [ 3 ]. We present a case of an abdominal wall abscess a year after laparoscopic cholecystectomy, demonstrating the importance of minimizing gallstone loss.…”
Section: Introductionmentioning
confidence: 99%
“…Patients usually present after months to years secondary to laparoscopic cholecystectomy with nonspecific signs and symptoms [ 7 ]. Despite that, cases of dropped stones are usually clinically asymptomatic [ 8 , 9 ]. Following a laparoscopic cholecystectomy, some prominent serious complications of stone spilling might develop.…”
Section: Introductionmentioning
confidence: 99%